(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Jasmine,the 1985-novel by Mukherjee, explores, in a radical and violent way, the danger– but also the potential – represented by displacements and uprootedidentities. In the novel, the pivotal play of migrations, forced and voluntary,literal and figurative, found in the plural female subjectivity of the youngprotagonist/narrator – initially named Jyoti Vijh – represents the dislocationand progress within the tangled framework of the protagonist’s/narrator’spersonal history, a 24-year history that moves with astonishing speed from thePunjabi village of Hasnapur to the urban centre of Jullundhur, to the GulfCoast of Florida, to a Hindu ghetto in Queens, to upper-class Manhattan, to thefarming landscapes of small-town Baden, in Iowa, and finally to California, ina certain way closing successfully Jyoti’s journey from East to West.